What Levels of Racial Diversity Can Be Achieved with Socioeconomic‐Based Affirmative Action? Evidence from a Simulation Model. (6th April 2018) - Reardon, Sean F.; Baker, Rachel; Kasman, Matt; Klasik, Daniel; Townsend, Joseph B.
Abstract: This paper investigates to what extent socioeconomic status (SES)‐based affirmative action in college admissions can produce racial diversity. Using simulation models, we investigate the racial and socioeconomic distribution of students among colleges under the use of race‐ or SES‐based affirmative action policies, or targeted, race‐based recruitment policies. We find, first, that neither SES‐based affirmative action nor race‐targeted recruiting on their own produce levels of racial diversity achieved by race‐based affirmative action. However, the two policies in combination, although likely expensive, may yield racial diversity comparable to race‐based affirmative action. Second, the use of affirmative action policies by some colleges reduces the diversity of similar‐quality colleges without such policies. Third, the combination of SES‐based affirmative action and race recruiting results in fewer academically‐overmatched Black and Hispanic students than under race‐based affirmative action, but the schools that use both also see a reduction in the academic achievement of enrolled students.